Failure case studies of fast ionization dynistors. (November 2021) - Huang, Xinyuan; Liang, Lin; Wang, Ganping; Qing, Zhengheng
Abstract: In this paper, the characteristics and causes of the failure of Fast Ionization Dynistors (FIDs) are analyzed. Die cracks are observed in cross-sectional images of the failed FIDs by Scanning Electron Microscopy (SEM). According to the characteristics of the observed die cracks, two different types of failure modes are proposed, and the possible causes are analyzed. A two-dimensional numerical model of the unit cell structure of FIDs based on the drift-diffusion model is established to simulate their switching process. Microcrack introduced in the preparation process of FIDs is found at the edge of one of the dies. The simulation shows that there is a local electric field intensity concentration phenomenon during the switching process that may cause microcracks to expand into cracks.